Pengaruh Pemberian Pakan Ikan Rucah Terhadap Pertumbuhan Ikan Kerapu Cantang (Epinephelus fuscoguttatus x Epinephelus lanceolatus) - M Hasan M Hasan; Tri Yulianto; Shavika Miranti (Intek Akuakultur, 2021)
This research was conducted from February to March 2020 for 35 days at the Pengujan Fish Seed Center (BBI), Bintan Regency, Riau Islands Province. The method used was experimental with a completely randomized design (CRD) with 4 treatments and 3 replications. Using data analysis with One-Way ANOVA shows that feeding trash fish to the growth of grouper fish. The parameters taken were absolute length growth with a value of 4.59±0.46cm with treatment B, absolute weight growth with a value of 24.62±2.47g treatment B, specific growth rate with a value of 0.70±0.07% treatment B, feed efficiency with a value of 38.13±3.62% of treatment A, the rate of feed conversion with a value of 8.57±3.62% of treatment C and the survival rate of grouper with a value of 100±0.00% of treatment C.